PENGGAMBARAN KARAKTER CHANG’E DALAM FILM “OVER THE MOON” - Natasya Andriana; Selvia Selvia (Haluan Sastra Budaya, 2023)
Myths and legends have been told from generation to generation by being spoken from thousands of years ago. Myth in Chinese language is Shen hua (神话), shen means god, spirit and holy; hua is a saying, a fairy tale, an oral story. In the movie “Over the Moon”, there are characters in Chang'e’s legend story, such as Hou Yi, even the Jade rabbit appears in the movie. The portrayal of Chang'e's character in the film has undergone several changes and “Alih Wahana” by filmmaker's. Therefore, researchers are interested in analyzing the depiction of Chang'e in the film "Over the Moon". The purpose of this research is to analyze the portrayal of Chang'e's character in the film "Over the Moon". This study uses qualitative research methods with data collection techniques in the form of documentation from the film "Over the Moon". The approach used is a narrative approach that focuses on the study of an individual. Chang'e's character in the film has changed from the story in the Chang'e legend, some of these changes are character and visual changes. Chang'e's character in the film is made narcissistic because of her loneliness, while Chang'e's visuals in the film are made attractive with bold makeup and magnificent and diverse clothing.